A battle of wits? Problem-solving abilities in invasive eastern grey squirrels and native Eurasian red squirrels. (March 2018) - Chow, Pizza Ka Yee; Lurz, Peter W.W.; Lea, Stephen E.G.
Abstract : Behavioural flexibility has been argued to be an evolutionarily favourable trait that helps invasive species to establish themselves in non-native environments. Few studies, however, have compared the level of flexibility (whether considered as an outcome or as a process) in mammalian invaders and related native species. Here, we tested whether flexibility differs between groups of free-ranging invasive eastern grey squirrels, Sciurus carolinensis, and native Eurasian red squirrels, Sciurus vulgaris, in the U.K., using an easy and a difficult food extraction task. All individuals of both species showed flexibility, at the outcome level, in solving the easy task and solution time was comparable between species across a series of successes. A higher proportion of grey squirrels than red squirrels solved the difficult task. However, for those squirrels that did solve the task, solving efficiency was comparable between species on their first success, and a few red squirrels outperformed the grey squirrels in subsequent successes. Between-species analysis showed that instantaneous flexibility, flexibility at the process level that was measured as the rate of switching between tactics after a failed attempt, was higher in red squirrels than in grey squirrels. Within-species analysis also revealed that red squirrel problem solvers showed higher flexibility at the process level than their nonsolver counterparts. Nonsolvers also failed to make 'productive' switches (switching from ineffective to effective tactics). Together, the results suggest that problem-solving ability overlaps in the two species, but is less variable, and on average higher, in grey squirrels than in red squirrels. The superior behavioural flexibility of the grey squirrels, shown here by success at problem solving, may have facilitated their invasion success, but it may also have resulted from selective pressures during the invasion process. Highlights: We compared grey and red squirrels' flexibility using two food extraction problems. All squirrels solved the easy task and showed comparable efficiency. More greys solved the difficult task, but were less efficient than reds. Red nonsolvers showed lower instantaneous flexibility than red solvers. Greys' problem-solving ability is less variable, and higher, than reds'.